Interplay of two major repair pathways in the processing of complex double-strand DNA breaks. - Dobbs, T; Palmer, P; Maniou, Z; Lomax, M; O'Neill, P (2008)
Radiation-induced complex double-strand breaks (DSBs) characterised by base lesions, abasic sites or single-strand breaks in close proximity to the break termini, are believed to be a major cause of the biological effects of ionising radiation exposure. It has been hypothesised that complex DSBs pose problems for the repair machinery of the cell. Using a biochemical approach, we have investigated the challenge to two major repair processes: base excision repair and ligation of DSB ends. Double-stranded oligonucleotides were synthesised with 8-oxo-7,8-dihydroguanine (8-oxoG) at defined positions relative to readily ligatable 3'-hydroxy or 5'-phosphate termini. The break termini interfere with removal of 8-oxoG during base excision repair as elucidated from the severely reduced efficiency of 8-oxoG removal by OGG1 with AP endonuclease-1 when in close proximity to break termini. NEIL-1, however, can partially restore processing of complex DSBs in an AP endonuclease-1 independent manner. The influence of 8-oxoG on ligation shows delayed rejoining if 8-oxoG is positioned two to three bases from the 3'-hydroxy or six bases from the 5'-phosphate termini. When two 8-oxoG lesions are positioned across the break junction ligation is severely retarded. This reduced efficiency of repair indicates that complex DSBs are likely to persist longer than simple DSBs in cells, and as a consequence are more significant in contributing to the biological effects of ionising radiation.